Epidimiologic Features of Brucellosis in Stavropol Region - D. V. Rusanova; G. I. Lyamkin (Проблемы особо опасных инфекций, 2009)
Analysis of many-years brucellosis morbidity in Stavropol region in 2001-2007 showed epidemiological situation to be tense, thus the deterioration of epizootiological and epidemiological conditions as regards brucellosis could be expected. Epidemiological zoning of Stavropol region according to the rate of risk of population infectioning with brucellosis allowed to discriminate territories with different degree of epidemiological danger. These data could be used during next 2-3 years for evaluation of brucellosis epidemiological situation while carrying out epidemiological analysis.